Ecology in the religion teaching programme for the II class of preparatory school - Łukomski, Julisław (Studia Ecologiae et Bioethicae, 2007)
The article presents a trial of including ecological contents to religion teaching programme in the II class of preparatory school. Ecological contents in this programme concern following issues: human ecology, natural parental planning, personal dimension of human activity in the universe, ecological values, solidarity of human and nature, patriotism in contemporary times, nation and family in the trend of eco-development.